2019
DOI: 10.1111/bcp.14116
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization as an opportunity to correct errors in anticoagulant treatment in patients with atrial fibrillation

Abstract: lant therapy among patients with atrial fibrillation (AF). Methods: Our cohort included patients admitted to our institution with a history of AF between 2016 and 2018. We categorized patient's treatment upon admission and discharge as lacking (no treatment despite indication), inadequate (according to individual characteristics) or adequate. We assessed adequacy of treatment upon discharge and determined factors associated with correcting admission errors. Results: Of 4427 patients admitted with a history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
14
0
3
Order By: Relevance
“…In France, a prospective nationwide cohort study in primary care reported that 39% of the patients received at least one inappropriate DOAC prescription, mostly were inappropriate underdosing [ 21 ]. Another cross‐sectional study of oral anticoagulant use in patients with AF demonstrated underdosing in 13.1% of prescriptions, and unfortunately, 39.4% of their patients had not been prescribed an indicated DOACs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In France, a prospective nationwide cohort study in primary care reported that 39% of the patients received at least one inappropriate DOAC prescription, mostly were inappropriate underdosing [ 21 ]. Another cross‐sectional study of oral anticoagulant use in patients with AF demonstrated underdosing in 13.1% of prescriptions, and unfortunately, 39.4% of their patients had not been prescribed an indicated DOACs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar prevalence was noted in another study from Israel, where DOAC underdosing was detected among 13% of hospitalized patients with AF. 41 A previous study has summarized the results of a review made by clinical pharmacists to DOAC orders among patients in our hospital. Nearly 30% of the consultations included recommendations for increasing the dose.…”
Section: Discussionmentioning
confidence: 99%
“…33 In a UK study which enrolled hospitalised patients with AF, only 32.6% had adequate OAC treatment on admission, with DOAC underdosing as the most common error. 34 Thirdly, less interaction with the healthcare system and less monitoring should be considered as factors. It has been shown that a warfarin clinic is associated with improved OAC adherence compared with community-based care.…”
Section: The Large Increase In Oac Utilisation In Ireland Has Been Reportedmentioning
confidence: 99%